(untitled) (International Journal of Studies in Nursing, 2018)
Background: Parkinson’s disease (PD) is the second most common neurodegenerative disease, after Alzheimer’s disease, affecting approximately one million persons aged 65 years and above in the United States. Parkinson’s disease represents a major medical concern for health professionals, national healthcare bodies and a heavy burden for caregivers. Heart failure occurred twice as frequently in elderly PD patients as in non-PD patients. There is paucity of information on the association of patient and hospital characteristics on the outcomes of inpatient with both congestive heart failure and Parkinson disease. Congestive Heart Failure with PD as a comorbidity will increase the cost of care and health resources. We investigate on the current prevalence and factors that affect the inpatient with both CHF and PD conditions using a longitudinal datasets from National Inpatient Samples. The results obtained from this study will provide information that will reduce frequent readmission, length of stay, total charges and mortality rate in this population. Methods: Data from the National Inpatient Samples (NIS) were extracted and analyzed using ICD 9 codes (CHF 428, PD 332) for the main diagnosis. For continuous variables, we calculated the mean and standard deviations and evaluated significant differences of these factors by Parkinson disease status using the t-test. For categorical variables, we obtained the counts (proportions) and evaluated significant differences using the Chi-square and Fisher’s exact test Propensity score was utilized to match age, gender and race using logistic model for hospital death and generalized linear model for length of stay (LOS) and hospital charges. Result: The overall frequency of Parkinson disease (PD) in congestive heart failure was 1.54 % (n = 10,748). PD patients with CHF were more likely to be males (53.13 %; 5462) and Caucasians (82.24 %; n=8454). The average age of inpatient was approximately 80 years (SD=8.05). Hospital admission, decreases with median household income. Patients with low income (1 - 38,999) were admitted more with 3002 (29.70%) than those with higher income (63,000 and more) with 2230 (22.06%). Length of stay (LOS) (p<0.0001) and total charge incurred during hospitalization were less in patients with PD (p< 0.005) (table 1). In these analyses, we found that patients with PD were discharged more from urban non-teaching hospital than urban teaching hospital (p<0.0001). Conclusion: The general characteristics and frequency of the participant in this study are summarized in Table I. Accordingly, characteristics of patients with congestive heart failure with or without Parkinson’s disease did not differ by age, gender, or ethnicity (P>1.000). Similarly, hospital death rates (%) were not different (P>1.000), although hospital length of stay (P<1.000) and total charge incurred during hospitalization were less in patients with PD (p < 0.005)